Courtyard configuration strategy to reduce air temperature in Malaysian university campus / Muhammad Noriman Mohd Fadzi, Sabarinah Sheikh Ahmad and Mariam Felani Shaari - Mohd Fadzi, Muhammad Noriman; Sheikh Ahmad, Sabarinah; Shaari, Mariam Felani (2018)
A Courtyard is an open space that is partly or completely surrounded by building walls. It acts as a microclimate modifier as it not only allows sunlight into the building but also helps to protect occupants from outdoor harsh conditions by reducing air temperature of its surrounding environment. Malaysia hot and humid climate is characterised by a high temperature, humidity and abundant of rainfall throughout the year. A courtyard design that is tailored to Malaysia climatic conditions could help improve thermal comfort of building occupants. The aim of this study is to identify factors that influence the reduction of air temperature within the courtyard for thermal improvement and to recommended strategies for hot and humid climate courtyard design. The study employed a quantitative approach. The investigations were conducted using ENVI-met simulation software, focused on the three courtyard factors that could influence the reduction of ambient air temperature, namely the orientation, shape and height, and vegetation. Results show that the three factors influence the improvement of shading effect within the courtyard, thus reduce the ambient air temperature reading for better occupant thermal comfort. In hot and humid climate countries such as Malaysia, shading effects are very important since the region is exposed to direct sunlight as the sun path is mostly overhead between 11:00 and 15:00. Hence, courtyard design strategies must be wisely considered during the early design stage using credible simulated findings.